Pengaruh Beban Kerja Dan Stres Kerja Terhadap Burnout - Chandra, Felix (Politeknik Negeri Ambon, 2024)
This research was conducted to determine the influence and magnitude of workload and work stress on employee burnout. This research is a type of explanatory research. This research was conducted at Hotel X, a three-star hotel in Ambon City. The population in this study was Hotel X employees, with a total of 40 employees. The number of samples in this study was 40 employees, determined using a saturated sampling technique, namely taking the entire population as a sample. The measurement scale used is the Likert scale. The data in this research was collected by distributing questionnaires to respondents. Multiple regression analysis is a data analysis technique used to test hypotheses. The data from the questionnaire was processed with the help of SPSS tools. The results of this study found that workload had a positive and significant effect on burnout, and work stress had a positive and significant effect on burnout.